Bibliografía española de Derecho penal (Abril-Septiembre de 2002) - Higuera Guimerá, Juan-Felipe; Alastuey Dobón, Carmen; Escuchuri Aisa, Estrella; Rueda Martín, Mª. Ángeles; Vizueta Fernández, Jorge; Mayo Calderón, Ana Belén; Fernández Ibáñez, Eva (Revista de Derecho Penal y Criminología, 2019)
-